Gambaran Perilaku Kader Pos Pelayanan Terpadu Balita dalam Deteksi Dini Stunting di Desa Sebatu Kecamatan Tegalalang Kabupaten Gianyar - Putu Diana Angelina; Ni Komang Erny Astiti; Ni Ketut Somoyani (Malahayati Nursing Journal, 2026)
ABSTRACT Stunting can interfere with brain development and growth, which increases the likelihood of developing chronic diseases when adults. Cadres have a crucial role in overcoming stunting in toddlers. Cadres are competent in detecting early stunting by measuring infant anthropometry. growth and development screening, growth screening and early detection by empowering toddler posyandu cadres. The results of the interview showed that the majority of cadres had never participated in special stunting training in anthropometric measurement training. The purpose of the study was to determine the behavior of toddler posyandu cadres in early detection of stunting. The study was conducted in April 2025. The research design was descriptive quantitative knowledge and attitudes of stunting detection and anthropometric measurement skills. The type of primary data obtained with instruments in the form of valid and reliable knowledge and attitude questionnaires and anthropometric measurement skills checklists according to Ministry of Health standards. All questionnaires were declared valid and reliable. Respondents were 45 posyandu cadres. The sampling method was with total sampling. Data analysis using univariate. The results showed that the knowledge of cadres was categorized as well-informed, the attitudes of posyandu cadres were categorized as positive. The skills of measuring the height of cadres were quite skilled, and the skills of measuring weight were quite skilled. The result of the behavioral score calculation is 75.26 which is included in sufficient behavior. The Sebatu Village Government should strive to optimize the skills of cadres in early detection of stunting in toddlers through training and development of cadres.  Keywords: Behavior, Posyandu Cadres, Skills, Stunting.  ABSTRAK Stunting dapat mengganggu perkembangan dan pertumbuhan otak, dimana meningkatkan kemungkinan ketika dewasa mengalami penyakit kronis. Kader mempunyai peran yang sangat krusial dalam mengatasi stunting pada balita di Indonesia. Kader bertugas mendeteksi dini stunting dengan mengukur antopometri bayi. skrining tumbuh kembang serta deteksi dini dengan pemberdayaan kader posyandu balita. Hasil wawancara diketahui mayoritas kader belum pernah mengikuti pelatihan stunting khusus dalam pelatihan pengukuran antropometri. Tujuan penelitian untuk mengetahui perilaku kader posyandu balita dalam deteksi dini stunting. Penelitian dilakukan pada bulan April 2025. Desain penelitian yaitu deskriptif kuantitatif pengetahuan dan sikap deteksi stunting serta keterampilan pengukuran antopometri. Jenis data primer yang didapatkan dengan instrumen berupa kuesioner pengetahuan dan sikap yang valid dan reliabel serta checklist keterampilan pengukurun antopometri sesuai standar Kemenkes. Semua kuesioner dinyatakan valid dan reliabel. Responden sebanyak 45 kader posyandu. Metode pengambilan sampel dengan total sampling. Analisis data menggunakan univariat. Hasil penelitian menunjukkan pengetahuan kader dikategorikan berpengetahuan baik, sikap kader posyandu dikategorikan dengan sikap positif. Keterampilan pengukuran tinggi badan kader cukup terampil, Keterampilan pengukuran berat badan cukup terampil. Hasil hitung skor perilaku yaitu 75,26 yang termasuk dalam perilaku cukup. Pemerintah Desa Sebatu agar berupaya mengoptimalkan keterampilan kader dalam deteksi dini stunting pada balita melalui pelatihan dan pengembangan kader.  Kata Kunci: Keterampilan, Kader Posyandu, Perilaku, Stunting.